Granule of BU-XIN RUAN-MAI Attenuates the Patients' Angina Pectoris of Coronary Heart Disease via Regulating miR-542-3p/GABARAP Signaling. (27th December 2019) - Yan, Dong; Zhao, Li-li; Yue, Bo-wen; Qian, Hui; Zhang, Zi-han; Wang, Ning; Yan, Shi-hai; Qian, Yu-liang
Abstract : Objective . Coronary heart disease (CHD) has been regarded as a serious and common disease in the modern society. This study aims to investigate the effect of Granule of BU-XIN RUAN-MAI (BXRM) on angina pectoris of coronary heart disease and to explore the molecular mechanisms underlying Granule of BU-XIN RUAN-MAI-mediated protective activity against this disease. Methods . The effects of Granule of BU-XIN RUAN-MAI on clinical symptoms of patients' angina were indicated by hemorheology indicators including high shear of blood viscosity, low shear of blood viscosity, plasma viscosity, erythrocyte rigidity index, D-D dimer, fibrinogen content, and lipid content. The effects of Granule of BU-XIN RUAN-MAI on isoprenaline-induced myocardial cell injury were determined by conducting H&E staining and by performing ELISA to examine the serum content of MDA, SOD, Na + /K + -ATPase, cAMP, and the content of inflammatory factors in isoprenaline-induced rats. Meanwhile, western blot and real time PCR were used to determine the expression of genes involved in oxidation and energy metabolism, and real time PCR was also used for determination of miR-542-3p expression. Luciferase reporter assay was conducted to test the binding sites of miR-542-3p on GABARAP 3′UTR. The chemical compositions of Granule of BU-XIN RUAN-MAI were determined by liquid LC-QTOF-MS. Results . Granule of BU-XIN RUAN-MAI significantly attenuated the clinical symptoms of patients' angina by improving the patients' heart rate and by decreasing the level of hemorheology indicators and also by reducing the serum content of TC, TG, LDL, and elevated HDL content. H&E staining demonstrated that Granule of BU-XIN RUAN-MAI ameliorated the myocardial ischemia in a dose-dependent manner. Besides, Granule of BU-XIN RUAN-MAI downregulated serum MDA content and upregulated the content of SOD, Na + /K + -ATPase, and cAMP in isoprenaline-induced rats. Granule of BU-XIN RUAN-MAI significantly improved oxidation stress by increasing PPAR α expression, and it inhibited inflammation by downregulating expression and contents of IL-6, IL-1 β, and TNF- α . Then, Granule of BU-XIN RUAN-MAI-containing serum increased the SOD content, and reduced the MDA content in angiotensin II-stimulated HUVEC cells. The granule of BU-XIN RUAN-MAI-containing serum obviously downregulated protein expressions of P40phox, P47phox, and P67phox in plasma membrane, and it significantly increased protein levels of P40phox, P47phox, and P67phox in the cytoplasm of HUVEC cells. Furthermore, GABARAP was reduced in heart tissues of ISO-induced rats and in angiotensin II-stimulated cell lines, and GABARAP was required for the inhibitory activity of Granule of BU-XIN RUAN-MAI on oxidation and inflammation in vivo and in vivo . GABARAP could be upregulated by Granule of BU-XIN RUAN-MAI by inhibiting the expression of miR-542-3p, which may significantly enhance oxidation and inflammation by targeting GABARAP in cardiomyocytes. Moreover, the silencing of GABARAP could obviously reverse the granule of BU-XIN RUAN-MAI-mediated protective activity against coronary heart disease, and interfering GABARAP expression also could partly block the anti-miR-542-3p-controlled oxidation and inflammation in cardiomyocytes. Besides, salidroside, loganin, and polydatin were the main compounds of granules of BU-XIN RUAN-MAI. Conclusion . Granule of BU-XIN RUAN-MAI is an excellent prescription for treatment of coronary heart disease by suppressing inflammation and NAPDH-mediated oxidative stress. The miR-542-3p/GABARAP axis is required for Granule of BU-XIN RUAN-MAI, exhibiting its protective activity against the pectoris of coronary heart disease.